Economic evaluation of aerobic exercise training in older adults with vascular cognitive impairment: PROMoTE trial. Issue 3 (29th March 2017) - Davis, Jennifer C; Hsiung, Ging-Yuek Robin; Bryan, Stirling; Best, John R; Eng, Janice J; Munkacsy, Michelle; Cheung, Winnie; Chiu, Bryan; Jacova, Claudia; Lee, Philip; Liu-Ambrose, Teresa
Abstract : Background/objectives: Evidence suggests that aerobic exercise may slow the progression of subcortical ischaemic vascular cognitive impairment (SIVCI) by modifying cardiovascular risk factors. Yet the economic consequences relating to aerobic training (AT) remain unknown. Therefore, our primary objective was to estimate the incremental cost per quality-adjusted life years (QALYs) gained of a thrice weekly AT intervention compared with usual care. Design: Cost–utility analysis alongside a randomised trial. Setting: Vancouver, British Columbia, Canada. Participants: 70 adults (mean age of 74 years, 51% women) who meet the diagnostic criteria for mild SIVCI. Intervention: A 6-month, thrice weekly, progressive aerobic exercise training programme compared with usual care (CON; comparator) with a follow-up assessment 6 months after formal cessation of aerobic exercise training. Measurements: Healthcare resource usage was estimated over the 6-month intervention and 6-month follow-up period. Health status (using the EQ-5D-3L) at baseline and trial completion and 6-month follow-up was used to calculate QALYs. The incremental cost–utility ratio (cost per QALY gained) was calculated. Results: QALYs were both modestly greater, indicating a health gain. Total healthcare costs (ie, 1791±1369 2015 CAD at 6 months) were greater, indicating a greater cost for the thrice weekly AT group compared with CON. From the Canadian healthcare system perspective, the incremental cost–utility ratios for thrice weekly AT were cost-effective compared with CON, when using a willingness to pay threshold of CAD 20 000 per QALY gained or higher. Conclusions: AT represents an attractive and potentially cost-effective strategy for older adults with mild SIVCI. Trial registration number: NCT01027858.